Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

DIFFICULT MATH QUESTION!! HELP NEEDED PLEASE!!?

Please solve the following simultaneous equations:

2x = 1 - 3y

3y^2 - x^2 = 2

Please do it step by step for explanation... thank you! :)

3 Answers

Relevance
  • 8 years ago
    Favorite Answer

    2x = 1 - 3y

    x = 1/2 - 3/2 y

    x = 0.5 - 1.5y ......... Eq. 1

    3y² - x² = 2 ............. Eq. 2

    Sub 0.5 - 1.5y from Eq. 1 for x in Eq. 2:

    3y² - (0.5 - 1.5y) = 2

    3y² - 0.5 + 1.5y = 2

    3y² + 1.5y = 2 + 0.5

    3y² + 1.5y = 2.5

    3(y² + 0.5y) = 2.5

    y² + 0.5y = 2.5 / 3

    y² + 0.5y = 0.833

    y² + 0.5y + 0.625 = 0.833 + 0.0625

    (y + 0.25)² = 0.896

    y + 0.25 = √0.896

    y + 0.25 = ± 0.947

    y = - 0.25 ± 0.947

    If y = - 0.25 + 0.947,

    y = 0.697

    and

    x = 0.5 - 1.5(0.697)

    x = 0.5 - 8.034

    x = - 7.534

    One Solution Set (- 7.534, 0.697)

    ¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨

    If y = - 0.25 - 0.947,

    y = - 3.733

    and

    x = 0.5 - 1.5(- 3.733)

    x = 0.5 - (- 5.6)

    x = 0.5 + 5.6

    x = 6.1

    Other Solution (6.1, - 3.733)

    ¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨

  • ?
    Lv 5
    8 years ago

    2x = 1 - 3y <=== lets call this equation A

    3y^2 - x^2 = 2 <=== equation B

    first solve for a variable (x or y) for one of the equations.

    2x = 1 - 3y <=== divide all terms by 2

    x = 1/2 - (3/2)y

    Plug in x = 1/2 - (3/2)y into equation B

    3y^2 - ((3/2)y)^2 = 2

    3y^2 - (9/4)y^2 = 2

    (12/4)y^2 - (9/4)y^2 = 2

    (3/4)y^2 = 2 <==== multiply both sides by 4/3

    y^2 = 2*(4/3)

    y^2 = 8/3 <==== square root both sides

    y = ±sqrt(8/3)

    Plug the value of y into equation A

    2x = 1 - 3(sqrt8/3) <=== divide all terms by 2

    x = (1/2) - (3/2)(sqrt8/3)

  • Peter
    Lv 4
    8 years ago

    2x = 1 - 3y

    Square both sides of this equation

    4x^2 = 1 - 6y + 9y^2

    You now have x^2 in terms of y, substitute this into 3y^2 - x^2 = 2 to give a quadratic in y. Solve for y, then find x from the first equation.

Still have questions? Get your answers by asking now.